In silico before in vivo: How to predict the heating efficiency of magnetic nanoparticles within the intracellular space - Sanz, Beatriz (2016)
This work aims to demonstrate the need for in silico design via numerical simulation to produce optimal Fe 3 O 4 -based magnetic nanoparticles (MNPs) for magnetic hyperthermia by minimizing the impact of intracellular environments on heating efficiency. By including the relevant magnetic parameters, such as magnetic anisotropy and dipolar interactions, into a numerical model, the heating efficiency of as prepared colloids was preserved in the intracellular environment, providing the largest in vitro specific power absorption (SPA) values yet reported. Dipolar interactions due to intracellular agglomeration, which are included in the simulated SPA, were found to be the main cause of changes in the magnetic relaxation dynamics of MNPs under in vitro conditions. These results pave the way for the magnetism-based design of MNPs that can retain their heating efficiency in vivo, thereby improving the outcome of clinical hyperthermia experiments.